2018
DOI: 10.1186/s12968-018-0445-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between myocardial extracellular volume and strain analysis through cardiovascular magnetic resonance with histological myocardial fibrosis in patients awaiting heart transplantation

Abstract: BackgroundCardiovascular magnetic resonance (CMR)-derived extracellular volume (ECV) and tissue tracking strain analyses are proposed as non-invasive methods for quantifying myocardial fibrosis and deformation. This study sought (1) to histologically validate myocardial ECV against the collagen volume fraction (CVF) measured from tissue samples of patients undergoing heart transplantation and (2) to detect the correlations between myocardial systolic strain and the myocardial ECV and histological CVF in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 42 publications
2
26
0
Order By: Relevance
“…The similar T 2 values of patients and controls in this study might be related to their ROI placement, since they explicitly excluded positive LGE segments from the ROI, while all other studies used the entire myocardium without excluding positive LGE segments [164][165][166][167][168][169]. Nevertheless, the T 2 values of positive and negative LGE segments were similar in all studies that reported T 2 values of both segments [166][167][168]. The overall meta-analysis confirmed the significantly higher T 2 values in DCM patients (SMD = 1.90, 95% CI [1.07, 2.72], P < 0.01, I 2 = 89%, Fig.…”
Section: Dilated Cardiomyopathymentioning
confidence: 90%
See 1 more Smart Citation
“…The similar T 2 values of patients and controls in this study might be related to their ROI placement, since they explicitly excluded positive LGE segments from the ROI, while all other studies used the entire myocardium without excluding positive LGE segments [164][165][166][167][168][169]. Nevertheless, the T 2 values of positive and negative LGE segments were similar in all studies that reported T 2 values of both segments [166][167][168]. The overall meta-analysis confirmed the significantly higher T 2 values in DCM patients (SMD = 1.90, 95% CI [1.07, 2.72], P < 0.01, I 2 = 89%, Fig.…”
Section: Dilated Cardiomyopathymentioning
confidence: 90%
“…The weighted mean T 2 values at 1.5 T in DCM patients was 62.9 ± 5.7 ms and 55.4 ± 3.5 ms in controls [164][165][166][167][168][169] (Table 1, Fig. 5).…”
Section: Dilated Cardiomyopathymentioning
confidence: 96%
“…More importantly, there is growing evidence that CMR-derived strain analysis is a predictor of adverse events in patients with nonischemic DCM [99][100][101]. In particular, global longitudinal strain analysis has independent and incremental prognostic value to other risk factors including LVEF, LGE, and ECV [99][100][101][102][103]. Peak circumferential strain in association with the absence of LGE and LV mass were found to be predictive of LVRR [104].…”
Section: Strain Analysismentioning
confidence: 99%
“…The association of myocardial native T1 or ECV estimates with diffuse myocardial fibrosis in systemic inflammatory diseases like sarcoidosis, systemic lupus erythematosus, rheumatoid arthritis, or systemic sclerosis is limited (Table 1), as increased native T1 and ECV values in these diseases reflect "myocardial edema-related" disease activity scores rather than "fibrosis-related" disease progression [2,[40][41][42]. Recognition of these acute stages in systemic inflammatory diseases could be supported by additional acquisition of myocardial T2 maps, depicting myocardial edema without major interference of myocardial fibrosis [2,43,44].…”
Section: Normal Left Ventricular Configurationmentioning
confidence: 99%
“…Numerous studies have reported globally increased native T1 and ECV values in both ischemic and non-ischemic DCM (Fig. 2 and Appendix B), limiting the ability to differentiate them using a quantitative scale [44,82]. Correlations of native T1 and ECV with histologic parameters in eccentric LV hypertrophy are controversial (Table 1 and Appendix A).…”
Section: Eccentric Left Ventricular Hypertrophymentioning
confidence: 99%